Review on Durability Study of Construction Materials and Techniques of Nagarathar - Manju R, Rashigasri K, Aishwaryalakshmi V (International Journal of Advanced Science and Technology, 2020)
The review on this topic is to study, durability of structures constructed using ancient techniques and modern techniques. The ancient construction techniques involve high durability of structure whereas in modern construction technique the durability of structure speaks less. Chettinad construction technique, a standing example for its durability was studied. The lime mortar and type of plastering carried out was the main reason for its durability. This study deals with the plastering technique involved in the ancient Chettinad construction